Significant hardness enhancement in an Al–Cu–Mg alloy with high Cu:Mg ratio by microalloying with Si and Ge - Castro Riglos, Maria Victoria (2018)
The evolution of hardness in an Al-Cu-Mg based alloy with high Cu:Mg ratio (= 2, at. %) microalloyed with Si and Ge was studied during artificial ageing treatment performed at 190 °C. The results were compared to those obtained in a similar alloy with no Mg content. The hardness evolution in the Mg containing alloy was similar to that of the Mg free alloy, but shifted by about 50 Hv to higher values for all ageing times. The peak hardness occurred after 3 h ageing in both alloys, with a value slightly above 200 Hv in the Mg containing alloy. The microstructure of the peak aged and the overaged condition were characterized by means of transmission electron microscopy (TEM). For the Mg-containing alloy the microstructure of the peak aged condition consisted of plate-shaped precipitates, with a very similar structure to that of the θ′ phase and a high density of small needle-shaped precipitates lying along the < 100 > Al directions. In the peak aged and overaged conditions the needle-shaped precipitates were found to belong to the Q′ phase (Al4Cu2Mg8Si7) or its precursor phases, previously observed in the Al–Mg–Si system with minor Cu additions.